The Influence of Parenting Patterns on Children's Learning Motivation - Mashurin, Mashurin; Wangid, Muhammad Nur; Futihaturrobiah, Futihaturrobiah (Universitas Ahmad Dahlan, 2023)
Parenting and learning motivation during the pandemic have become special concerns. This study aims to determine the effect of parenting on learning motivation during the pandemic. This study uses a quantitative approach with simple linear regression data analysis techniques. The population in this study is all seventh-grade students of public junior high schools in Lampung Timur. The sampling technique used is proportional stratified random sampling, involving 103 students. The instruments used are parenting and learning motivation questionnaires. The results of this study show that there is a positive and significant effect of parenting on learning motivation during the pandemic. The results of this study can be considered in the development of guidance and counseling services in junior high schools.